2020
DOI: 10.1111/1468-5973.12327
|View full text |Cite
|
Sign up to set email alerts
|

How would citizens react to official advice in a nuclear emergency? Insights from research in three European countries

Abstract: Nuclear emergencies confront decision‐makers, emergency actors and publics with several challenges, many of which are related to social, ethical and communication aspects. Based on empirical data from three European countries, this paper investigates citizens' potential behaviour in an emergency situation. It analyses relationships between self‐assessed compliance with protective actions and a number of variables, including knowledge about protective actions, trustworthiness of communicators, perceived social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 91 publications
1
6
0
Order By: Relevance
“…Several studies also found barriers for EMS personnel to be concerned for family safety, particularly their perceived ability to communicate with family members, especially during periods of extended shifts or events that keep them away from home (DiMaggio et al, 2005;Noble et al, 2014;Turner et al, 2020). Another study suggests that, in a nuclear emergency, most responders expect to follow actions advised by authorities, except for leaving their children at school (Turcanu et al, 2020). As we have seen in the COVID-19 pandemic, risk to first responders and healthcare workers is a primary concern due to the worldwide shortage, or PPE (D'Ambrosio, 2020; Kalkman, 2021).…”
Section: Sdmentioning
confidence: 99%
“…Several studies also found barriers for EMS personnel to be concerned for family safety, particularly their perceived ability to communicate with family members, especially during periods of extended shifts or events that keep them away from home (DiMaggio et al, 2005;Noble et al, 2014;Turner et al, 2020). Another study suggests that, in a nuclear emergency, most responders expect to follow actions advised by authorities, except for leaving their children at school (Turcanu et al, 2020). As we have seen in the COVID-19 pandemic, risk to first responders and healthcare workers is a primary concern due to the worldwide shortage, or PPE (D'Ambrosio, 2020; Kalkman, 2021).…”
Section: Sdmentioning
confidence: 99%
“…In addition, organizations and authorities in charge of managing the crisis should elicit trust from the public (De Vocht et al, 2016). Research has, for example, illustrated that higher trust in authorities can increase compliance with official advice during nuclear emergencies (Turcanu et al, 2021). Organizations must therefore know to what degree crisis information is able to increase trust.…”
Section: The Power Of Information In Times Of Crisismentioning
confidence: 99%
“…In a nuclear accident scenario, a major uncertainty is how citizens will act [ 11 ]. From an expert perspective, the average person tends to overreact to the risk of radiation exposure [ 12 ]. For instance, if authorities instruct citizens to shelter in their homes after an incident, many will still voluntarily evacuate [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study analyzed survey data ( N = 2291) from Sweden, a country that operates nuclear power plants that supply 39% of the country’s electricity [ 24 ]. The analysis drew on one of the most well-established theories dealing with citizens’ emergency behaviors, the Protective Action Decision Model (PADM) [ 12 , 23 ], which, to our knowledge, had yet to be applied to the Northern European region.…”
Section: Introductionmentioning
confidence: 99%